IQ versus befolyásolás, avagy az intelligencia hányados és a befolyásolhatóság közötti összefüggések - Siket, Zsuzsanna (Debreceni Jogi Műhely, 2012)
This is an essay about the connection of impressionability and intelligence quotient. The intelligence quotient of witness or accused has main role in the criminal procedure. So, what is the intelligence and the intelligence quotient? The intelligence is a mental power, that contains the quality of argumentation, contemplation, learning, problem solution and the abstract thinking. This mental power helps to understand the happenings in the world. The intelligence quotient of the witness or accused is very important, because the quality of perception is based on the intelligence quotient. The perception shows how they can remember the criminal situations. The intelligence quotient depedns on the the social and cultural enviornment, the inherited qualities, and the personal experiences. The important question is, which is the stronger, the intelligence or the impressionability. High intelligence quotient is a mean of the witness or accused to escape form impressionability. On the other hand, the authorities try to use the power of influence. So two powers meet in the criminal procedure, the intelligence and the influenceing, and usually the stronger is the winner. The intelligence quotient has main role in the part of the investigation and the trial. The warnings before the interrogation are written in the difficult language of law. So it would be a problem in the part of investigation, because the witness or accused does not understand these. Because of that they would say or tell something that they would not tell in normal circumstances. The low intelligence makes the accused confess their real or believed sin. The accused with higher intelligence quotient understands much better the warning, and they can use those possibilites the law premits them. Their combinative quality is higher, so they discover another solutions not just the confessing. The authorities shall pay attention to the intelligence quotient of the accused, because the extremly low intelligence quotient would be the sign of mental retardation. The mental retardation is a kind of pathological mental state. The accused who suffers in pathological mental state is not be punishable or his or her punishment may be reduced unlimited. The language of trials is also difficult and the other problem with it is publicity. The accused with low IQ feels shame because of their low IQ so they want to keep it secret. The accused becomes stressed in the trial so they lose their second chance to make things better, because they are not able to confess without impressions again. Low intelligence quotient usually cooperates with low ability of problem solution, so the accused with low intelligence can’t adapt themselves to the occassion of the trial. This circumstance would influence the judges, when they impose punishment, so the punishment would be stricter. The conclusion is that the accused with low intelligence quotient meets with some difficulties during the criminal procedure, so the consuels for the defence shall pay attention to them, and help their clients with comments of the legal texts. On the other hand, the authorities shall be out for the good knowledge of mankind.